OPTIMIZING THE LECTURE METHOD TO ENHANCE STUDENTS' INTERACTION AND LEARNING INTEREST IN THE DIGITAL ERA - Rendy S. Sambara; Fahmi; Gesika Avelina (Adisam Publisher, 2026)
This study aims to examine how the lecture method can be optimized to enhance student interaction and learning interest in the digital era. This study is motivated by the current phenomenon in which the lecture method is often perceived as less effective due to its predominantly one-way communication, leading to student boredom and, consequently, a decline in learning interest. This research employed a qualitative approach using a library research design by reviewing scholarly articles and other relevant and credible sources. The findings indicate that the lecture method remains relevant in contemporary education when combined with digital technology and interactive instructional strategies to improve learning effectiveness. Several strategies that contribute to the effectiveness of the lecture method include promoting interactive learning, utilizing digital media, and integrating the lecture method with other instructional approaches, such as interactive discussions and project-based learning. Furthermore, teachers' readiness and pedagogical competence in implementing these strategies play a crucial role in determining their success. Therefore, optimizing the lecture method through technology-based and interactive approaches can significantly enhance student participation and learning interest in the digital era.